2011
DOI: 10.1172/jci44303
|View full text |Cite
|
Sign up to set email alerts
|

mTOR-mediated dedifferentiation of the retinal pigment epithelium initiates photoreceptor degeneration in mice

Abstract: Retinal pigment epithelial (RPE) cell dysfunction plays a central role in various retinal degenerative diseases, but knowledge is limited regarding the pathways responsible for adult RPE stress responses in vivo. RPE mitochondrial dysfunction has been implicated in the pathogenesis of several forms of retinal degeneration. Here we have shown that postnatal ablation of RPE mitochondrial oxidative phosphorylation in mice triggers gradual epithelium dedifferentiation, typified by reduction of RPE-characteristic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

22
309
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 278 publications
(332 citation statements)
references
References 86 publications
22
309
1
Order By: Relevance
“…A similar down-regulation of visual cycle genes was observed after retinal detachment created in mice (8). Injection of sodium iodate (NaIO 3 ), an oxidizing agent known to induce selective RPE cell death followed by retinal degeneration, resulted in down-regulation of RPE65, LRAT, and RLBP1 within 2 days (9,10). These findings support the idea that pan-down-regulation of visual cycle genes may be a general response of RPE cells to stress (8).…”
supporting
confidence: 68%
“…A similar down-regulation of visual cycle genes was observed after retinal detachment created in mice (8). Injection of sodium iodate (NaIO 3 ), an oxidizing agent known to induce selective RPE cell death followed by retinal degeneration, resulted in down-regulation of RPE65, LRAT, and RLBP1 within 2 days (9,10). These findings support the idea that pan-down-regulation of visual cycle genes may be a general response of RPE cells to stress (8).…”
supporting
confidence: 68%
“…In addition to intracellular metabolites, we also analyzed the Ringer's solution in the apical and basolateral compartments of these hfRPE for 13 C metabolites. We found that hfRPE cells incubated with [1][2][3][4][5][6][7][8][9][10][11][12][13] C]palmitate alone released significantly more (7-fold) labeled ␤-HB (75.2 Ϯ 49.7 pmol/cm 2 RPE in a 500-l volume over 3 h) into the apical chamber compared with the basal chamber (10.5 Ϯ 18.3 pmol/cm 2 RPE in a 1500-l volume over 3 h) (Fig. 3E).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the publicly available mouse microarray data (GSE10246, Ref. 6) revealed that mouse RPE expresses particularly high levels of mitochondrial HMG-CoA synthase 2 (Hmgcs2), the key enzyme required for ketone production (7). Hmgcs2 mRNA is also abundant in two other tissues, liver and colon, both of which are known sites of ketogenesis (8).…”
mentioning
confidence: 99%
“…RPE cells are exposed to ongoing oxidative stress from the combined effects of light, choroidal O 2 , polyunsaturated fatty acids, and retinoids (6). The resulting impairment in RPE energy metabolism and function by oxidative stress is one likely mechanism for the pathogenesis of AMD (3,(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Mitochondria support the active energy metabolism of the RPE (10)(11)(12). A recent report showed that RPE is less stable and less able to support the retina when it is forced to rely on glycolytic rather than mitochondrial metabolism (13).…”
mentioning
confidence: 99%